The THE INDONESIAN STUDENTS’ WILLINGNESS TO COMMUNICATE IN VIRTUAL CLASS: A CASE STUDY - Lodya Sesriyani (Getsempena English Education Journal, 2020)
As one of the keys to quality instructional process, students’ willingness to communicate deserves a place to observe especially when it was done by non-English department students when conducting instructional practices virtually during the Covid-19 outbreak. The present study aimed at investigating the students’ willingness to communicate during TOEFL preparation classes. The object of this study was 30 students of Economics Education Study Program in their second semester learning in a South-Tangerang based university, Indonesia. The students’ patterns in their willingness to communicate were examined using close observation within 3 consecutive meetings. Due to the pandemic outbreak of Covid-19, the instructional process was conducted virtually via Zoom platform. One lecturer acted as the instructor and one passive observant was given an access to record and observe the instructional practices. This study revealed that the students’ willingness to communicate depends on the task type given by the lecturer. It indicated the significance of intelligible and feasible instruction in order that the students’ willingness to communicate improved.